DIGITALISASI SISTEM ADMINISTRASI AKADEMIK SEBAGAI UPAYA PENINGKATAN MUTU LAYANAN DI IAIN CURUP - Yusman Haris; Dwi Oktasari; Jenny Fransiska; Murniyanto Murniyanto; Muhammad Istan; Beni Azwar; Destriani Destriani (Jurnal Manajemen Pendidikan, 2026)
The quality of academic administration services in higher education significantly influences academic community satisfaction and institutional effectiveness. However, several State Islamic Religious Higher Education Institutions (PTKIN) still rely on manual administrative systems, creating challenges in meeting the demand for responsive digital services. This study aims to analyze the implementation of academic administration digitalization at IAIN Curup, identify its supporting and inhibiting factors, and evaluate its impact on service quality improvement. This research employed a qualitative case study approach involving 28 participants, including lecturers, educational staff, and students selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation analysis of SIAKAD reports from 2020–2024. The findings indicate that digitalization covered online registration, KRS services, grade management, academic reporting, and digital correspondence. Service efficiency increased by 68.4%, while student satisfaction rose from 61.2% to 84.7%, highlighting the importance of sustainable digital transformation in the Society 5.0 era.